SIL (Altre Modernità, 2021)
In this issue, we return to our “reviews from the future”: to recall the SIL Residential Seminar, cancelled in 2020 due to the pandemic, we re-read with Maria Giovanna Sardu Il romanzo del divenire, which was published from the proceedings of the summer seminar held in Trevignano in 2002. Michela Marocco, on the other hand, tells us about the new volume resulting from the national literary competition Lingua Madre, which for sixteen years now has been telling the story of migration in Italy from the point of view of women.